Study on the pathogenesis of PLXNB1 gene in olfactory dysfunction of allergic rhinitis - Xinglong Chen; Lingqiong Zhao; Wenlong Luo (PLoS ONE, 2026)
Background Olfactory dysfunction (OD) is a common yet underrecognized symptom of allergic rhinitis (AR). While inflammation contributes to OD, the underlying molecular mechanisms remain unclear. Methods Differential gene expression analysis was conducted using GEO datasets (GSE75011 and GSE43523). OD DEGs were identified and used to construct a protein-protein interaction (PPI) network. Key genes were filtered through LASSO regression and validated through immune infiltration analysis. The biological function of PLXNB1 was further investigated via in vitro human nasal epithelial cell models and an in vivo mouse model of AR. Results PLXNB1 expression was significantly downregulated in AR patients compared to healthy controls in both training and validation datasets. Immune infiltration analysis revealed a negative correlation between PLXNB1 and pro-inflammatory immune cells. Functional assays showed that PLXNB1 knockdown led to increased expression of inflammatory cytokines (e.g., IL-4, IL-6), likely via activation of the MAPK/p38 signaling pathway. Conversely, overexpression or Desloratadine treatment restored PLXNB1 levels and suppressed inflammation. Conclusion PLXNB1 is a potential hub gene linking immune dysregulation to olfactory dysfunction in AR. Its downregulation exacerbates inflammation and may impair olfactory function via the MAPK/p38 axis. These findings offer new insights into AR pathogenesis and identify PLXNB1 as a promising target for therapeutic intervention.